Analysis Of Garbage Retribution Information System At Bumdes Kaligayam Talang Tegal Regency - alfiyah, fuji (Media Jurnal Informatika, 2025)
The garbage retribution payment system in Kaligayam Village was still conducted manually, causing delays in reporting, data loss risks, and lack of transparency. This study aimed to analyse the existing garbage retribution information system and propose an efficient digital solution. The research employed direct observation, interviews with the leader of Neighborhood Association (RT), the BUMDes treasurer, and village officials, as well as literature review. Analysis was conducted using SWOT methodology and workflow mapping through Flow of Document. The results revealed that while the manual system benefited from strong social structure, it suffered from administrative inefficiencies. Therefore, a web-based system was recommended to enable automatic payment recording, real-time reporting, and improved accuracy and citizen participation in garbage retribution management.